IRF4 is required for migration of CD4+ T cells to the intestine but not for Th2 and Th17 cell maintenance - Schmidt, Constantin; Harberts, Aenne; Reimers, Daniel; Bertram, Tabea; Voß, Leonie Caroline; Schmid, Joanna; Lory, Niels Christian; Spohn, Michael; Koch-Nolte, Friedrich; Huber, Samuel; Raczkowski, Friederike; Breloer, Minka; et al. (Frontiers in Immunology, 2023)
The transcription factor Interferon Regulatory Factor 4 (IRF4) is central in control of T cell activation and differentiation. Deficiency of IRF4 results in severe immune deficiency and affects maturation and function of most if not all T cell subsets. Here we use mouse infection models for Citrobacter rodentium and Strongyloides ratti to analyze the function of IRF4 in T helper (Th) 17 and Th2 cell responses, respectively. IRF4 deficient mice were impaired in the control of both pathogens, failed to mount Th17 and Th2 cell responses and showed impaired recruitment of T helper cells to the intestine, the infection site of both pathogens. Compromised intestinal migration was associated with reduced expression of the intestinal homing receptors α4β7 integrin, CCR9 and GPR15. Identification of IRF4 binding sites in the gene loci of these receptors suggests a direct control of their expression by IRF4. Competitive T cell transfer assays further demonstrated that loss of one functional Irf4 allele already affected intestinal accumulation and Th2 and Th17 cell generation, indicating that lower IRF4 levels are of disadvantage for Th2 and Th17 cell differentiation as well as their migration to the intestine. Conversion of peripheral CD4+ T cells from an Irf4 wildtype to an Irf4 heterozygous or from an Irf4 heterozygous to a homozygous mutant genotype after C. rodentium or S. ratti infection did not reduce their capacity to produce Th17 or Th2 cytokines and only partially affected their persistence in the intestine, revealing that IRF4 is not essential for maintenance of the Th2 and Th17 phenotype and for survival of these T helper cells in the intestine. In conclusion, we demonstrate that the expression levels of IRF4 determine Th2 and Th17 cell differentiation and their intestinal accumulation but that IRF4 expression is not crucial for Th2 and Th17 cell survival.